PERTUMBUHAN, HASIL DAN TOLERANSI GENOTIP PADI TERHADAP PENYAKIT HAWAR DAUN (Bacterial Leaf Blight) PADA APLIKASI DOSIS Paenibacillus Polymixa BERBEDA - Ai Komariah; Eva Lady Mustika (Paspalum: Jurnal Ilmiah Pertanian, 2016)
The research was to study the effect of genotype rice plants and Paenibacillus Polymixa dose to growth, yields and genotype  tolerances to  BLB (Bacterial Leaf Blight) deseases.The research was conducted in the village Kedawung Majalaya Karawang District of West Java in the rainy season, from Januari 2015 until  Mei 2015.  The  experiment was  used Strip plots design with genotypes of rice was the main plot consist of  Sri Putih (v1), Manohara (v2) and  IR 64 (v3), subplots were doses paenybacilus polymixa (d1 ) Dose Paenybacillus polymixa 0 liters / ha, (d2) Dose Paenybacillus polymixa 2.5 liters / ha (5 ml / liter), (d3) Dose Paenybacillus polymixa 5 liters / ha (10 ml / liter) and (d4) Dose Paenybacillus pol ymixa 7.5 liters / ha (15 ml / liter).  The results of the experiment shosed that no interaction between the administration of the dose variation Paenybacillus polymixa with genotype rice plants against rice yields and not interaction between administration of the dose variation Paenybacillus polymixa with genotype rice plants to suppress the intensity of the attack Bacterial leaf blight disease. For the intensity of the disease, dose applications Paenybacillus polymixa 2.5 liters / ha (5 ml / liter) was effectively used during the vegetative age of 21, 28 and 35 days after planting.